Toxicological and biochemical studies for chlorpyrifos insecticide on some mosquito larvae and their associated predators. Issue 1 (31st December 2022) - Mohammed, Shaimaa H.; Eltaly, Randa I.; Salem, Hend H.
ABSTRACT: Use of chemical insecticide with natural enemies could be more effective in mosquito control strategy. This study examined the toxicity of chlorpyrifos insecticide against three field-collected mosquito species, Culex pipiens, Anopheles pharoensis and Ochlerotatus caspius and their associated predators dragonfly ( Pantala flavescens ) and mayfly ( Caenis stephens ) naiads as non- target insect for chlorpyrifos. The predation potential of Pa. flavescens and Ca. stephens against tested mosquito larvae was also investigated. Additional biochemical assays were carried out to detect the effect of chlorpyrifos on some detoxifying enzymes of tested mosquito larvae and their associated predators. The results showed that ( Pa. flavescens) have higher predation potential than ( Ca. stephens ). The toxicological results recorded high toxic effect of chlorpyrifos on Ca. stephens followed by An. pharoensis and Oc. caspius with percent mortality 100, 90 and 85% respectively, while Pa. flavescens exhibited high resistance followed by Cx. pipiens with percent mortality 20 and 40% respectively. Moreover, Acetylcholinesterase and glutathione S-transferase were significantly increased only in Cx. pipiens and Pa. flavescens . It could be concluded that, chlorpyrifos have different toxicological effect on the tested mosquito larvae and associated predators. So, the side effect of chlorpyrifos must be taken in consideration before using it in control programs.